Hiperrealitas Musik dalam Peluang Pedagogis di Era Disrupsi : Penelitian - Bayu Aji Wicaksono; Setyo Yanuartuti; Warih Handayaningrum (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article examines the transformation of music's meaning and function in the digital disruption era through the lens of Jean Baudrillard’s hyperreality framework. Algorithmically curated digital music such as